Experiences of patients with Breast Cancer in Selecting Conventional and Complementary Therapies in Remote Areas: A Qualitative Study - Senudin, Putriatri Krimasusini; Padeng, Eufrasia Prinata; Laput, Dionesia Octaviany; Raden, Natalia Damayanti Putri; Trisnawati, Reineldis E.; Nanur, Fransiska Nova (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: The selection of therapy is a challenging issue to overcome. The selected therapy must be based on the condition of breast cancer patients and has advantages such as increasing life expectancy, being able to overcome the symptoms and complaints of breast cancer patients and improving the quality of life. This study aimed to explore the experiences of people with breast cancer regarding the reasons for choosing therapy, namely complementary and conventional therapies.Methods: This study was qualitative research with a descriptive phenomenological study approach. Participants obtained using purposive sampling techniques were included until the data was saturated. Research data was collected through in-depth interviews conducted in a semi-structured manner. The thematic analysis used in this study consisted of several stages using the Colaizzi method.Results: This study illustrated that complementary and conventional therapies were beneficial to cancer treatment. The three themes from the analysis results included the benefits of complementary and conventional therapies, access to therapy and treatment costs. The choice of therapy depended on available access and costs for breast cancer treatment.Conclusion: People with breast cancer in remote areas choose complementary therapies, such as herbal medicine, meditation, reflexology, and acupuncture as the first choice and conventional therapies, such as surgery and chemotherapy as alternative therapies. This is because the choice of therapy also depends on the ease of access to treatment and the availability of costs for breast cancer patients.